Environmental risk factors for asthma in 13-14 year old African children - Ayuk, Adaeze Chikaodinaka (Department of Paediatrics and Child Health, 2019)
BACKGROUND: Asthma prevalence in African children is high and increasing, with more severe disease than that in high income countries. Specific factors driving the rising prevalence or disease severity are poorly understood. The aim of this study was to investigate environmental factors associated with asthma and severity in African children using data obtained from International Study of Asthma and Allergies in Childhood, (ISAAC) III. METHODS: A population based cross-sectional study of children aged 13-14 years from 10 African centres who participated in ISAAC III from randomly selected schools. The prevalence of asthma or severe asthma was calculated for each centre. Self-reported environmental exposures included engaging in physical exercise, television watching, biomass and ETS exposure, consumption of paracetamol, large family sizes and having pets in the home. Univariable and multivariable analyses were done adjusting for centre variations. Odds ratio and respective 95% confidence intervals (CI) were calculated. RESULTS: Amongst 28490 adolescents from 232 schools in 10 African centres (4 middle income and 6 low income), the prevalence of asthma was 12.8% (CI 12.4-13.2), while prevalence of severe disease was 8.7% (CI 8.4-8.0). Factors most strongly associated with asthma were maternal smoking (OR= 1.41; 95% CI: 1.23 - 1.64), exposure to open fire heating (OR=1.28; 95% CI: 1.08 - 1.51) and electric heating (OR=1.13; 95% CI: 1.01 - 1.28), engaging in strenuous exercise (OR= 1.29; 95% CI: 1.11 - 1.50 and monthly use of paracetamol (OR 1.23; 95% CI 1.13 - 1.33, while having an elder sibling was protective for asthma (OR=0.87; 95% CI 0.77 – 0.98). Factors strongly associated with severe asthma were maternal smoking (OR=1.61; 95% CI: 1.38 - 1.89), having a cat pet at home (OR=1.14; 95% CI: 1.04 - 1.25), engaging in≥3 weekly physical exercise (OR=1.42; 95% CI: 1.23 - 1.64) and monthly consumption of paracetamol (OR=1.20; 95% CI: 1.07 - 1.34). CONCLUSION: There was a high prevalence of severe asthma in African children. Several environmental exposures were associated with asthma or with severe disease. Strategies to reduce harmful environmental exposures must be strengthened to reduce the burden of childhood asthma in Africa.